Correction: Maarof et al. Biodegradable Carbonate Apatite Nanoparticle as a Delivery System to Promote Afatinib Delivery for Non-Small Cell Lung Cancer Treatment. Pharmaceutics 2022, 14, 1230 - Nian N. N. Maarof; Emilia Abdulmalek; Sharida Fakurazi; Mohd Basyaruddin Abdul Rahman (MDPI AG, 2024)
In the original publication, there was a mistake in the legend for "Figure 3" [...]